The Philosophy of Education and Upbringing as the Quintessence of Women's Emancipation - HAMBARDZUMYAN, Naira; PARSADANYAN, Siranush (WISDOM, 2022)
The paper focuses on the philosophical and socio-historical subtexts of the ideas on education and upbringing in Constantinople in the late 19th century and early 20th centuries, with examples from the works of Armenian female authors: Elpis Kesaratsian, Srbuhi Tyusab, Sipil, Haykanush Mark, Zapel Yesayan. According to them, the main historical and philosophical prerequisites for changing attitudes towards women’s education and upbringing relate not only to women but also to men. The aim of the paper is to study the issues of women’s indisputable right to education and upbringing, their natural learning abilities and opportunities as the quintessence of emancipation formed in Constantinople. The problem of the study is to show the philosophical subtext of the establishment of institutions for women’s education and upbringing, the organization of education, as well as the processes of overcoming the patriarchal tradition through education. This kind of study has been attempted for the first time. Since the 50s-60s of the 19th century, not only the nature of work and status of women but also the issues of their education and upbringing had special significance in Constantinople.